2004
DOI: 10.1111/j.1532-5415.2004.52251.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Nonmalignant Pain and Analgesic Prescribing Patterns in Elderly Nursing Home Residents

Abstract: In nursing home residents, persistent pain is highly prevalent, there is suboptimal compliance with geriatric prescribing recommendations, and acute pain may be an important contributing source of persistent pain. More effective provider education and research is needed to determine whether treatment of acute pain could prevent persistent pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
179
3
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(199 citation statements)
references
References 34 publications
9
179
3
8
Order By: Relevance
“…This was consistent with a study conducted by Miro et al 9 which states that women complain of pain more than men, and the sites of grievances are joint, lower extremities, spine and neck. 9 Additionally, paracetamol is the most prescribed analgesic in older adult patients at Puskesmas Tanjungsari in 2013, this is in accordance with a study conducted by Won et al 10 which states that of the administration of analgesic drugs, the most common are paracetamol (37.2%), propoxyphene (18.2%), hydrocodone (6.8%), and tramadol (5.4%). 10 This is strengthened also by a study conducted by Barber et al 11 which states that paracetamol is an analgesic drug that tends safe to be consumed because it has low side effects on gastric and kidneys function.…”
Section: Discussionsupporting
confidence: 73%
“…This was consistent with a study conducted by Miro et al 9 which states that women complain of pain more than men, and the sites of grievances are joint, lower extremities, spine and neck. 9 Additionally, paracetamol is the most prescribed analgesic in older adult patients at Puskesmas Tanjungsari in 2013, this is in accordance with a study conducted by Won et al 10 which states that of the administration of analgesic drugs, the most common are paracetamol (37.2%), propoxyphene (18.2%), hydrocodone (6.8%), and tramadol (5.4%). 10 This is strengthened also by a study conducted by Barber et al 11 which states that paracetamol is an analgesic drug that tends safe to be consumed because it has low side effects on gastric and kidneys function.…”
Section: Discussionsupporting
confidence: 73%
“…Won et al [37] reported that persistent pain was very high in those with musculoskeletal pain and those with a history of falls, fracture or surgery. This therefore suggests that these may be important variables to better identify those who are at greater risk of experiencing pain within a care home.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent strengths across the evidence-base were that the studies clearly presented a research question (n=23), recruitment was clearly presented and appropriately recruited in all but three studies [24,29,35], the assessment of musculoskeletal pain was clearly presented and followed an accurate method in all but 10 studies [10,21,22,24,25,28,33,34,37,39]. Whilst studies also reported the results to the previous evidence, and provided results and reporting of findings to permit the generalisability of these to the general population in seven papers (Table 3).…”
Section: Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Their responsibilities include knowing when and why to give or withhold certain high-risk medications. Nurses who treat individuals with chronic pain for example, which is prevalent in 4984% of nursing home residents, must follow strict guidelines with patient safety the priority [Bureau of Health Professions, 2010;Won et al 2004]. Nurses also commonly encounter problems that can affect compliance such as residents having difficulty swallowing or refusing the medication.…”
Section: Communication At the Interfaces Of Carementioning
confidence: 99%